Association between aberrant amino acid metabolism and nonchromosomal modifications fetal structural anomalies: A cohort study - Yuan, Huizhen; Liu, Chang; Wang, Xinrong; Huang, Tingting; Liu, Danping; Huang, Shuhui; Wu, Zeming; Liu, Yanqiu; Yin, Peiyuan; Yang, Bicheng (Frontiers in Endocrinology, 2023)
More than half of the cases of fetal structural anomalies have no known cause with standard investigations like karyotype testing and chromosomal microarray. The differential metabolic profiles of amniotic fluid (AF) and maternal blood may reveal valuable information about the physiological processes of fetal development, which may provide valuable biomarkers for fetal health diagnostics. This cohort study of singleton-pregnant women had indications for amniocentesis, including structural anomalies and a positive result from maternal serum screening or non-invasive prenatal testing, but did not have any positive abnormal karyotype or chromosomal microarray analysis results. A total of 1580 participants were enrolled between June 2021 and March 2022. Of the 1580 pregnant women who underwent amniocentesis, 294 were included in the analysis. There were 137 pregnant women in the discovery cohort and 157 in the validation cohort. High-coverage untargeted metabolomic analysis of AF revealed distinct metabolic signatures with 321 of the 602 metabolites measured (53%) (false discovery rate, q < 0.005), among which amino acids predominantly changed in structural anomalies. Targeted metabolomics identified glutamate and glutamine as novel predictive markers for structural anomalies, their vital role was also confirmed in the validation cohort with great predictive ability, and the area under the receiver operating characteristic curves (AUCs) were 0.862 and 0.894 respectively. And AUCs for glutamine/glutamate were 0.913 and 0.903 among the two cohorts. Our results suggested that the aberrant glutamine/glutamate metabolism in AF is associated with nongenetic fetal structural anomalies. Based on our findings, a novel screening method could be established for the nongenetic fetal structural anomalies. And the results also indicate that monitoring fetal metabolic conditions (especially glutamine and glutamate metabolism) may be helpful for antenatal diagnosis and therapy.